2003
DOI: 10.1002/marc.200350001
|View full text |Cite
|
Sign up to set email alerts
|

Mechanistic Investigation into the Unique Orientation Textures of Poly(vinylidene fluoride) in Blends with Nylon 11

Abstract: Self‐seeded crystallization experiments were carried out to detect the mechanism of the unique orientation behavior of poly(vinylidene fluoride) (PVDF) in oriented PVDF/nylon 11 blends. It was found that primary nuclei have no effects on the final orientation textures adopted by PVDF. The results show that the PVDF crystal orientation in the oriented blends is determined in the early stage of crystal growth, thus a trans crystallization mechanism is preferred.Isothermal crystallization kinetics for the self‐se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…Finally, in addition to the size of confined space, we also note that the confinement environment can also play an important role in inducing polar phases for PVDF . If the confinement environment provides a polar substrate for molten PVDF to crystallize, such as KBr/NaCl, mica, organo-modified clays, carbon nanotubes, or even immiscible polar polymers [nylon-11 and polyacrylonitrile (PAN) , ], polar phases can be obtained for PVDF. However, if the confinement environment provides a nonpolar substrate for molten PVDF to crystallize (e.g., PSF and PS) and the size of confined space is large enough, the nonpolar α phase will be obtained .…”
Section: Resultsmentioning
confidence: 96%
“…Finally, in addition to the size of confined space, we also note that the confinement environment can also play an important role in inducing polar phases for PVDF . If the confinement environment provides a polar substrate for molten PVDF to crystallize, such as KBr/NaCl, mica, organo-modified clays, carbon nanotubes, or even immiscible polar polymers [nylon-11 and polyacrylonitrile (PAN) , ], polar phases can be obtained for PVDF. However, if the confinement environment provides a nonpolar substrate for molten PVDF to crystallize (e.g., PSF and PS) and the size of confined space is large enough, the nonpolar α phase will be obtained .…”
Section: Resultsmentioning
confidence: 96%
“…123,124 When blending ferroelectric PA11 and PVDF, the glass transition temperature and melting point of PA11 decreases with increasing PVDF concentration, due to the dipolar intermolecular interactions between the polar amide groups (-NH-CO-) in PA11 and the polar -CF 2 groups in PVDF. 121,125 It has also been found that the hydrogen-bonded structure of PA11 becomes more disordered as the PVDF concentration is increased. The PVDF developed a larger proportion of polar band g-phase in blends with a high PA11 concentration compared to pure PVDF under similar melt quench conditions.…”
Section: Structure Of Polyvinylidene Uoride (Pvdf) and Polymorphsmentioning
confidence: 99%
“…Recently, a unique orthogonal orientation, where polymeric chains align perpendicular to the drawing direction, has been occasionally reported in heterogeneous systems such as block copolymers, immiscible blends and organic/inorganic composites. Several models involving the epitaxial crystallization,8–10 thermal shrinkage stress,11,12 confinement of crystal growth,13–21 and trans‐crystallization22,23 have been employed to interpret such a behavior. However, it has rarely occurred in homogenous systems.…”
Section: Introductionmentioning
confidence: 99%